Vivencias de las madres que tienen un hijo con Síndrome de Down - Isla Amaya, Zulma Analí (2011)
This work study aims to uncover the experiences of mothers about having a child with Down syndrome, seeking to discover and understand the essence of the phenomenon interviewed 15mothers of children with Down syndrome in the city of San Pedro de Lloc, this research Inico May 1 to July 12, 2011. The coursemethodology used was the phenomenological perspective ofMartin Heidegger. The guiding question was posed to them: Tell me in detail what you live and how you live the mother of a child withDown syndrome (a)? process corresponded to the hermeneuticanalysis, which was considered the description and reduction, the development of units of meaning, analysis, and finally mediumvague and hermeneutic analysis itself. The findings show that thesemothers live an ex-sist, marked by uncertainty about the future for their children, from that perspective they feel authentic to live with them that future planning and the support given by the spouse and family . It is believed necessary to implement nursing interventionsfrom the initial design stage for these mothers so that the processhas suitable maternal them.